Associations of Metabolic Syndrome and Abdominal Obesity with Anion Gap Metabolic Acidosis among US Adults - Lambert, Douglas C.; Kane, Jamie; Slaton, Anthony; Abramowitz, Matthew K. (Kidney360, 2022)
Visual Abstract Key Points Waist circumference and metabolic syndrome features were associated with greater risk of anion gap metabolic acidosis and its components. Findings were preserved after excluding CKD (eGFR <90 ml/min per 1.73 m2 or urine albumin to creatinine ratio ≥30 mg/g). Clear associations were evident for anion gap metabolic acidosis, but not for nonanion gap metabolic acidosis. Background Obesity is a recently identified risk factor for metabolic acidosis and anion gap elevations in the absence of CKD. Metabolic acidosis is a treatable condition with substantial adverse effects on human health. Additional investigations are needed to characterize at-risk populations and explore potential mechanisms. We hypothesized metabolic syndrome (MetS) and waist circumference (WC) would be closely associated with this pathology. Methods Adult participants from NHANES 1999-2018 meeting study criteria were compiled as main (n=31,163) and fasting (n=12,860) cohorts. Regression models adjusted for dietary acid, eGFR, and other factors examined associations of WC and MetS features with anion gap metabolic acidosis and its components (serum bicarbonate ≤23 mEq/L and anion gap >95th percentile). Results Greater WC and MetS features were associated with progressively lower bicarbonate, higher anion gap, and greater odds ratios (OR) of metabolic acidosis (MA) and anion gap metabolic acidosis (AGMA). Compared with the reference, participants with the highest WC had ORs for MA and AGMA of 2.26; 95% CI, 1.96 to 2.62 and 2.89; 95% CI, 1.97 to 4.21; those with three and four versus zero MetS features had ORs for AGMA of 2.52; 95% CI, 1.95 to 2.94 and 3.05; 95% CI, 2.16 to 3.82. Associations of body mass index with outcomes were attenuated or absent after adjustment for WC or MetS. Findings were preserved after excluding eGFR <90 ml/min per 1.73 m2 and albuminuria. A lower MA cutoff (<22 mEq/L) raised the estimate of association between MetS and MA (OR for three and four vs zero features: 3.56; 95% CI, 2.53 to 5.02 and 5.44; 95% CI, 3.66 to 8.08). Conclusions Metabolic diseases are characterized by metabolic acidosis and anion gap elevations. Metabolic dysfunction may predispose patients without CKD to systemic acidosis from endogenous sources. Comprehensive acid-base analyses may be informative in patients with metabolic diseases.